Gender, Incumbency and Party List Nominations. Issue 1 (11th June 2018) - Meserve, Stephen A.; Pemstein, Daniel; Bernhard, William T.
Abstract : This study assesses how political parties' candidate selection strategies influence women's descriptive parliamentary representation. Focusing on proportional elections, it explores what determines whether parties place women in viable list positions. Evaluating party rankings at the individual level, it directly examines a mechanism – party nomination – central to prevailing explanations of empirical patterns in women's representation. Moreover, it jointly evaluates how incumbency and gender affect nomination. This study uses European Parliament elections to compare a plethora of parties, operating under numerous institutions, in the context of a single legislature. It finds that gender differences in candidate selection are largely explained by incumbency bias, although party ideology and female labor force participation help explain which parties prioritize the placement of novice women.